Correlation between Na/K ratio and electron densities in blood samples of breast cancer patients - Topdagi, Omer; Toker, Ozan; Bakirdere, Sezgin; Bursalioglu, Ertugrul Osman; Oz, Ersoy; Eyecioglu, Onder; Demir, Mustafa; Icelli, Orhan (SPRINGER, 2018)
The main purpose of this study was to investigate the relationship between the electron densities and Na/K ratio which has important role in breast cancer disease. Determinations of sodium and potassium concentrations in blood samples performed with inductive coupled plasma-atomic emission spectrometry. Electron density values of blood samples were determined via ZXCOM. Statistical analyses were performed for electron densities and Na/K ratio including Kolmogorov-Smirnov normality tests, Spearman's rank correlation test and Mann-Whitney U test. It was found that the electron densities significantly differ between control and breast cancer groups. In addition, statistically significant positive correlation was found between the electron density and Na/K ratios in breast cancer group.
Keywords: Blood samples; Breast cancer; Na/K ratio; Electron density; ICP-AES; SODIUM-POTASSIUM RATIO; PRESSURE; HYPERTENSION; ASSOCIATION; INTERSALT; TRANSMISSION; MORTALITY; EXCRETION; TISSUES; ADULTS; Biochemistry & Molecular Biology